Experience with a massive transfusion protocol in the management of massive haemorrhage. Issue 2 (21st March 2013) - Sinha, R.; Roxby, D.; Bersten, A.
Summary Background and objectives A massive transfusion response (MTR) was introduced in 2007 to provide blood and blood products in a timelier manner. Aim of this study was to determine whether implementation of the MTR was associated with a change in clinical practice or mortality. Materials and methods All MTR activations from 2008 to 2011 were included in the study. Patients who had received a massive transfusion (MT ≥ 10 units RBC in 24 h) as part of the MTR (MT‐MTR) were compared with a historical group of MT patients (MT‐Pre‐MTR) from 2004 to 2006. Blood product usage including fresh frozen plasma (FFP) : RBC and platelet : RBC ratios and mortality were compared between the two groups. Results Out of 169 MTR activations, 13 patients (8%) did not use any blood products, 73 (43%) used <10 units of RBC in a 24‐h period and 83 received a MT. The median number of units of FFP and platelets transfused in the MT‐MTR group were 10 [interquartile range (IQR) 7–17] vs 6 (5–10) [P < 0·001] and 3 (IQR 2–4) vs 2 (IQR 1–3) [P < 0·001] in the MT‐Pre‐MTR group of patients, respectively. The MT‐MTR group received a higher 24‐h FFP : RBC ratio (1 : 1·4 vs 1 : 2·4, P < 0·001). Overall mortality between the MT‐MTR and MT‐Pre‐MTR groups (29% vs 23%, P = 0·43) and 90‐day mortality was 25% vs 29% (P = 0·40), respectively. Conclusion Although there has been a significant change in transfusion practice in MT patients using a MTR, no change in mortality could be documented using such a protocol.